2020
DOI: 10.1029/2020gl090131
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Outliers in Lower Stratospheric Water Vapor Over North America Observed by MLS: Relation to Overshooting Convection Diagnosed From Colocated Aqua‐MODIS Data

Abstract: Convectively injected water vapor (H 2 O) in the North American (NA) summer lowermost stratosphere results in significant outliers in the 100-hPa H 2 O measurements from the Aura Microwave Limb Sounder (MLS). MLS statistics from 15 years confirm that the NA region contains over 60% of global 100-hPa H 2 O > 12 ppmv, despite having only ∼1.8% of all MLS observations. A profile sampled in August 2019 stands out, with H 2 O = 26.3 ppmv, far exceeding the prior record and the median ∼4.5-ppmv abundance in NA. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 47 publications
(58 reference statements)
0
12
0
Order By: Relevance
“…Their convective overshooting origin is unambiguously supported by both the enhanced isotopic ratios in the moist plumes and by their traceability to convective events. Notably, the occurrence of lower stratospheric moist plumes above the monsoon regions is also supported by satellite observations (Fu et al, 2006;Schwartz et al, 2013;Werner et al, 2020), whereas the enhanced water isotopic ratios observed over these regions (Hanisco et al, 2007;Randel et al, 2012) support the role of overshooting convection in maintaining the water vapour maximum in the summer monsoon anticyclones. This process adds to 455 the radiatively-driven slow ascent of wet air through the warm tropopause in the northern part of AMA.…”
mentioning
confidence: 55%
“…Their convective overshooting origin is unambiguously supported by both the enhanced isotopic ratios in the moist plumes and by their traceability to convective events. Notably, the occurrence of lower stratospheric moist plumes above the monsoon regions is also supported by satellite observations (Fu et al, 2006;Schwartz et al, 2013;Werner et al, 2020), whereas the enhanced water isotopic ratios observed over these regions (Hanisco et al, 2007;Randel et al, 2012) support the role of overshooting convection in maintaining the water vapour maximum in the summer monsoon anticyclones. This process adds to 455 the radiatively-driven slow ascent of wet air through the warm tropopause in the northern part of AMA.…”
mentioning
confidence: 55%
“…Three natural pathways for direct injection of H 2 O into the stratosphere exist: overshooting convection, pyrocumulonimbus (pyroCb) storms, and volcanic eruptions. The previous stratospheric H 2 O record measured by MLS was 26.3 ppmv at 100 hPa associated with an overshooting convective event in August 2019 that spanned thousands of square kilometers and persisted for several hours (Werner et al, 2020). Two pyroCbs stand out in the MLS H 2 O record: the 2017 Pacific Northwest (Pumphrey et al, 2021) and the 2019/2020 Australian New Year's (Kablick et al, 2020;Khaykin et al, 2020;Schwartz et al, 2020) events.…”
Section: Unprecedented Stratospheric H 2 O Injectionmentioning
confidence: 86%
“…Three natural pathways for direct injection of H 2 O into the stratosphere exist: overshooting convection, pyrocumulonimbus (pyroCb) storms, and volcanic eruptions. The previous stratospheric H 2 O record measured by MLS was 26.3 ppmv at 100 hPa associated with an overshooting convective event in August 2019 that spanned thousands of square kilometers and persisted for several hours (Werner et al., 2020 ). Two pyroCbs stand out in the MLS H 2 O record: the 2017 Pacific Northwest (Pumphrey et al., 2021 ) and the 2019/2020 Australian New Year's (Kablick et al., 2020 ; Khaykin et al., 2020 ; Schwartz et al., 2020 ) events.…”
Section: Unprecedented Stratospheric H 2 O Injectionmentioning
confidence: 96%